PECULIARITIES OF THE INITIAL STAGE OF PRE-TRIAL INVESTIGATION OF CRIMINAL OFFENSES IN THE FIELD OF TAXATION COMMITTED BY BUSINESS ENTITIES - Milimko, Larysa; Zhydovtsev, Iaroslav (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to give description to the initial stage of pre-trial investigation of criminal offences in the field of taxation, which is accomplished by the subjects of pre-trial investigation, to reduce problems and make suggestions of improvement of legislation in relation to the settlement of this sphere of legal relationships. Research methods: the research is conducted using the following methods analysis, synthesis, comparison. Results: based on the analysis of the state of regulatory and legal support, the positions of scientists, and practical workers, a description of the stage of the criminal process is given - the violation of a pre-trial investigation of criminal offenses in the field of taxation, committed by business entities. In particular, it was established that the Criminal Procedure Code adopted in 2012 simplified the procedure for starting a pre-trial investigation. But this led to the emergence of a number of problematic issues: the lack of a mechanism for checking statements and reports on criminal offenses; the impossibility of challenging the investigator’s activity of entering information about a criminal offense into the Unified Register of Pretrial Investigations leads to abuses by pretrial investigation bodies. Entering data on a committed crime in the field of taxation is possible only in the presence of an agreed tax notice-decision. Neither analytical reports nor experts’ conclusions create an obligation to pay tax, in addition, any tax information available in information and analytical databases, in this case, is not proper evidence in the sense of the procedural law. Currently, there is no criminal case initiated against the officials of the business entity in the field of taxation and according to the results of scheduled inspections, as there is a moratorium on their conduct, although changes are expected according to draft law No. 8401. In order to prevent excessive pressure on business entities in order to create favorable conditions for conducting economic activity (especially during the period of martial law and the post-war period), when investigating crimes at the initial stage, it is advisable to proceed from the principle of sufficiency of evidence for the initiation of a criminal case. Only if there is sufficient evidence, data should be entered into the Unified Register of Pretrial Investigations.